Conceptualization of Multicultural-Based Blended Learning with Flipped Classroom Model: Implications for Collaborative Problem Solving: Konseptualisasi Blended Learning Berbasis Multikultural dengan Model Flipped Classroom: Implikasi Terhadap Kemampuan Pemecahan Masalah Kolaboratif - Wulandari , Ria; Shofiyah, Noly; Kurniawan, Machful Indra (Universitas Muhammadiyah Sidoarjo, 2022)
The advantages of blended learning are flexibility and a personalized learning environment. A personalized learning environment is an effort to improve the quality of learner learning based on the diversity of the learner, one of which is cultural background. The diversity possessed by learners, especially cultural differences, needs to be taught to foster mutual respect, tolerance, and awareness to behave in a humanist, pluralist, and democratic manner which can be implemented through multicultural education. Previous research has not described cultural diversity in designing learning in blended learning. The purpose of writing this article is to develop a conceptual framework for blended learning based on multiculturalism using the flipped classroom model and its implications for collaborative problem-solving. The method used is a literature study.